Pengaruh Penyuluhan Melalui Media Leaflet Terhadap Tingkat Kepatuhan Remaja Putri Dalam Mengkonsumsi Tablet Fe - Salim, Ika Lestari; Harnaningsi, Harnaningsi; Diniaty Rosidi, Indah Yun; Hermawati, Hermawati (Madu : Jurnal Kesehatan, 2024)
Provision of iron supplement tablets for adolescent girls of at least 60 mg of elemental iron (in the form of furamate or Ferro Gluconate) and 0.50 mg of folic acid for adolescent girls aged 12-18 years in educational institutions (junior high school and senior high school or equivalent) and for suburban women (WUS) aged 15-49 years. Although the percentage of adolescent girls who received iron supplement tablets in Southeast Sulawesi reached 81%, there are still challenges in increasing its fulfillment. This study aims to determine the effect of counseling through leaflet media on the level of compliance of adolescent girls in consuming Fe tablets. This study uses quantitative research with a pre-experimental design type with a group pre-test and post-test research plan, namely this plan contains a pre-test before receiving treatment, after being given treatment, counseling is carried out through leaflet media and at the end of the activity a post-test is given. After conducting the research, the results of the Wilcoxon test showed that there was an effect of counseling through leaflet media on the level of compliance of adolescent girls in consuming Fe tablets, with a P value = 0.00 <0.05, which means that Ha is accepted and H0 is rejected. There is an effect of counseling through leaflet media on the level of compliance of adolescent girls in consuming Fe tablets.